Enhancing Spatial Memory: Anxiolytic and Antidepressant Effects of Tapinanthus dodoneifolius (DC) Danser in Mice. (5th February 2014) - Harquin Simplice, Foyet; David Emery, Tsala; Hervé Hervé, Ngatanko Abaissou
Abstract : We evaluated the anxiolytic and antidepressant effects of the aqueous extract of the bark of Tapinanthus dodoneifolius (TAE) (Danser) (25, 50, and 100 mg/kg), using open field, elevated plus maze, and forced swimming tests. Effect of TAE was compared to standard drugs diazepam (2 mg/kg) and imipramine (10 mg/kg). Additionally, the same doses of TAE were evaluated on rat's memory using Y-maze task. Results showed a significant (P < 0.05 ; 100 mg/kg) increase in the percentage of open arm entry and the time spent in the open arms in the elevated plus maze, suggesting an anxiolytic activity of the extract. In a dose-dependant manner, TAE at 25 mg/kg significantly (P < 0.05 ) decreased the number of lines crossed and the rearing behavior in the open field test, suggesting its possible sedative activity. In the forced swimming test, the immobility time of the animal was significantly reduced (P < 0.05 ) by TAE (100 mg/kg), compared to control, and this effect was quite comparable to that of imipramine. In the Y-maze paradigm, TAE at 50 mg/kg caused a significant increase in the spontaneous alternations but with a significant decrease in exploratory behavioral pattern. Taking these results together, TAE improved the spatial memory and showed anxiolytic, antidepressant, and sedative activities. The present results support the anxiolytic and antidepressant activities of TAE and, to our knowledge, for the first time, demonstrate its enhancing effect on memory.